2021
DOI: 10.1101/2021.10.24.465522
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the use of facial and neck cooling to improve indoor occupant thermal comfort in warm conditions

Abstract: Face and neck cooling has been found effective to improve thermal comfort during exercise in the heat despite the surface area of human face and neck regions accounts for only 5.5% of the entire body. Presently, very limited work in the literature has been reported on face and neck cooling to improve indoor thermal comfort. In this work, two energy-efficient wearable face and neck cooling fans were used to enhance occupant thermal comfort in two warm indoor conditions (30 & 32 °C). Local skin temperatures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Van Gaever et al reported that current technical standards on heating, ventilation, and air conditioning (HVAC) fail to provide a comfortable thermal environment for all members of surgical staff in the OR [28]. Moreover, it should be considered that there is a need to look for better wearable personal cooling systems to improve local body cooling while working in indoor environments, as reported by Yang et al, who investigated personal thermal management systems (PTMSs) [29]. However, despite the assumption that thermal comfort also plays a decisive role in the therapeutic outcome and in the surgical performance of the operators, there is still a lack of data in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…Van Gaever et al reported that current technical standards on heating, ventilation, and air conditioning (HVAC) fail to provide a comfortable thermal environment for all members of surgical staff in the OR [28]. Moreover, it should be considered that there is a need to look for better wearable personal cooling systems to improve local body cooling while working in indoor environments, as reported by Yang et al, who investigated personal thermal management systems (PTMSs) [29]. However, despite the assumption that thermal comfort also plays a decisive role in the therapeutic outcome and in the surgical performance of the operators, there is still a lack of data in this regard.…”
Section: Discussionmentioning
confidence: 99%